Subjective Well-Being of Overseas Students at the State University of Malang - Al Hafiz, Akbar Anwaretino; Tibrisna, Nashra; Paramarta, Nata Adyana; Edy, Dewi Fatmasari (Universitas Negeri Malang, 2023)
Overseas students experience various new problems in the overseas environment. The problems experienced can be from loneliness to difficulty adapting. This research aimed to determine the differences in subjective well-being between overseas and local students based on age group, gender, and coping strategies used by overseas students at the State University of Malang. The research method used is a mixed method consisting of comparative quantitative methods with 54 respondents and phenomenological qualitative methods with four respondents. The instruments used are the Satisfaction With Life Scale (SWLS), with a reliability value of .948 and validity ranging from .903 to .975, and the Positive Affect Negative Affect Schedule (PANAS) scale, with a reliability value of .889 for positive affect and .905 for negative affect and has validity ranging from .445 to .838 for positive affect and .646 to .838 for negative affect. The results of the analysis show that there is no significant difference in subjective well-being between overseas students and local students (p equal to .272), and there is also no significant difference in terms of gender (p equal to .626) or age. Furthermore, the coping strategy used by overseas students to overcome their problems is to do their favorite activities and gather with their friends. The findings support that other factors can affect overseas students’ subjective well-being, including social support, social relationships, and technological developments.